Biomarkers of fatigue related to adjuvant chemotherapy for breast cancer: evaluation of plasma and lymphocyte expression. Issue 1 (14th February 2015) - Cruz, Felipe M; Munhoz, Bruna A; Alves, Beatriz CA; Gehrke, Flavia S; Fonseca, Fernando LA; Kuniyoshi, Renata K; Cubero, Daniel; Peppone, Luke J; del Giglio, Auro
Abstract: Background: Fatigue is common in cancer patients receiving adjuvant chemotherapy. To further understand the mechanism of fatigue and search for potential biomarkers, we conducted this prospective study. Methods We enrolled breast cancer (BC) patients before their first adjuvant Adriamycin‐based chemotherapy cycle. Patients responded to the brief fatigue inventory (BFI) and Chalder fatigue questionnaires and had their blood drawn for both plasma evaluation and evaluation of the peripheral mononuclear cell fraction (PMNCF) mRNA expression of various biomarkers. We evaluated FSH, LH, estradiol, DHEA, DHEAS, IL6, IL2, ILIRA, IL1β, CRP, Cortisol in the plasma and IL2, IL10, IL6, TGF‐β, KLRC1, TNF, BTP, SNCA, SOD1, BLNK, PTGS2 and INF γ expression in the PMNCF. Results: 11 patients did not exhibit an increase in their BFI scores and served as controls, whereas 32 patients exhibited an increase in their BFI scores compared with the baseline scores. From the biomarkers we evaluated in the PMNCF, the only one significantly associated with fatigue was TGF‐β (p = 0.0343), while there was a trend towards significance with KLRC1 (p = 0.0627). We observed no evidence of significant associations of any plasma biomarkers with the development of fatigue. However when we analyzed patients with more severe fatigue, plasma IL1‐RA levels correlated directly with higher fatigue scores (p = 0.0136). Conclusions: We conclude that fatigue induced by chemotherapy in BC patients is associated with changes in IL1‐ra plasma levels and in TGF‐β lymphocyte expression. Its mechanism may be different than that observed in long‐term BC survivors or that induced by radiation therapy. Trial registration: NCT02041364 [ClinicalTrials.gov]